CAPACITY OF THE ISLAMIC BANKING MARKET - S. Kairdenov; O. Patlasov (Вестник СибАДИ)
The authors consider in this scientific publication features the origin and development of Islamic banking. This paper presents a theoretical and practical material on the principles and laws of the existence of an Islamic bank, as well as the proposed integrative processes and influencing factors of ethical principles of Islam in the traditional banking system. The article is devoted to the integration processes of introduction of Islamic finance in the global economy, based on the increasing demand for Islamic investment funds. The estimation of potential market Islamic banking products. It is proved that ethical finance are able to absorb the contours of the global financial crisis. The development of the Islamic banking system is based on the requirement of finding a new strategy to improve the existing mechanism and economic niches of Islamic banking.